If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) = 4(x + -1) Reorder the terms: 6(-2 + x) = 4(x + -1) (-2 * 6 + x * 6) = 4(x + -1) (-12 + 6x) = 4(x + -1) Reorder the terms: -12 + 6x = 4(-1 + x) -12 + 6x = (-1 * 4 + x * 4) -12 + 6x = (-4 + 4x) Solving -12 + 6x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -12 + 6x + -4x = -4 + 4x + -4x Combine like terms: 6x + -4x = 2x -12 + 2x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + 2x = -4 + 0 -12 + 2x = -4 Add '12' to each side of the equation. -12 + 12 + 2x = -4 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = -4 + 12 2x = -4 + 12 Combine like terms: -4 + 12 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 2+3[5-4x]=17+4[4x-1] | | -7+h=12 | | 25x-18=51+2x | | 25x-18=51+2x | | x-0.8=8.83 | | x-0.8=8.83 | | 3*-3=-3*+-3 | | -6z=72 | | -4=.05r-5 | | 1.5x-6=21 | | -23n=-46 | | 12.1=-19.3-4d | | 5q=-75 | | 3x-=4x-2(4-x) | | x^2-2x^4+1=0 | | 3a+2-5=14 | | 16-50= | | 5-t=23 | | 12m-17=13 | | 6x+x-32=8x-6-3x | | x^6-6x^3-16=0 | | 8y+6-5y=6+2y-10 | | 9*(8z-5)= | | 6(x+1)=3(x-6) | | 5x+2(x+10)=83 | | 6x+5x-2x+17x=117 | | -5.6=y-8 | | a+5+8=20 | | c=210+c | | 9(8z-5)= | | x+8=57 | | d=.75d |